A 3-year Longitudinal Study of Pocket Money, Eating Behavior, Weight Status: The Childhood Obesity Study in China Mega-Cities - Ma, Lu (Int J Environ Res Public Health, 2020)
The associations between children’s pocket money and their eating behaviors and weight status have not been examined using longitudinal data in China. Examined child and parental factors associated with children’s pocket money, and longitudinal effects of pocket money on children’s eating behaviors and weight status. Data were collected in 2015, 2016, and 2017 from 3261 school-age children and their parents in mega-cities across China (Beijing, Shanghai, Nanjing, Xi’an, Chengdu). Children’s weight, height, and waist circumference were measured; pocket money and eating behaviors were self-reported. Mixed effect models were used. Older children received more pocket money than younger children (incident rate ratio (IRR) = 1.21, 95% confidence interval (CI): 1.15, 1.26). Fathers gave their children more pocket money than mothers did (IRR = 1.22, 95% CI: 1.16, 1.30). Children with fathers having ≥ college education received more pocket money than the others did (IRR = 1.20, 95% CI: 1.04, 1.40). Some nutrition-related parenting behaviors and attitude were also associated with children’s pocket money. Compared with children receiving no weekly pocket money, those having 1–10 or 10–30 or >30-yuan weekly pocket money were 12.0–136% more likely to consume unhealthy foods and were 66–132% more likely to be overweight or obese. Some child and parental factors were associated with children’s pocket money, which increased risks of having unhealthy eating behaviors and being overweight and obese.